The ‘Be Cancer Alert Campaign’: protocol to evaluate a mass media campaign to raise awareness about breast and colorectal cancer in Malaysia - Schliemann, Désirée; Donnelly, Michael; Dahlui, Maznah; Loh, Siew Yim; Tamin Ibrahim, Nor Saleha; Somasundaram, Saunthari; Donnelly, Conan; Tin, Tin Su (BioMed Central, 2018)
BACKGROUND: Breast and colorectal cancer are the two most common cancers in Malaysia. Low awareness coupled with stigma and erroneous beliefs delay help-seeking behaviours, lead to late presentation and contribute to poor detection rates. Promoting cancer awareness through mass media may be effective in improving cancer-related knowledge and uptake in screening tests. However, research is sparse regarding the cultural translation and implementation of mass media campaigns in Malaysia (and Asia) in terms of raising awareness about colorectal and breast cancer. METHODS: A collaborative partnership comprising researchers from Malaysia and the UK as well as policy makers, public health experts and non-government organisations from Malaysia was formed to design, deliver and evaluate the Be Cancer Alert Campaign. Each awareness-raising campaign will run for five weeks (Colorectal Cancer in April 2018, followed by Breast Cancer in October 2018). Evaluation of the campaigns will take place in Gombak district (Colorectal Cancer) and Petaling district (Breast Cancer) respectively, in the form of a pre-post randomly selected household survey and collection of service utilisation data. Occupants who are aged 40-years and above and are able to answer questions independently will be selected from each household. A sample of 730 with 80% power will detect a change of 6.09% in knowledge that unexplained lump or swelling is a symptom of breast cancer or changes in bowel habits is a symptom of colorectal cancer. DISCUSSION: Malaysia and most South-East Asian countries have a low middle-income economy, with limited resources for cancer control. Late-staged cancers impose a significant economic burden on patients, households, communities, employers, health systems and governments. Our proposed strategy for the implementation of the culturally sensitive mass media cancer awareness-raising campaign will serve as a blueprint for cancer prevention and control policy in South-East Asian countries where the burden of cancer is increasing and there are high cancer death rates.